A moderate static magnetic field enhances TRAIL‐induced apoptosis by the inhibition of Cdc2 and subsequent downregulation of survivin in human breast carcinoma cells. Issue 5 (20th February 2014) - Lin, Tingting; Wan, Ling; Qi, Xin; Shi, Wenlong; Lin, Jun
<x xml:space="preserve">Abstract</x> Tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL) exhibits its potent antitumor activity via membrane receptors on cancer cells without deleterious side effects for normal tissue. However, as many other cancer types, breast cancer cells develop a resistance to TRAIL. In the present study, we reported that exposure to 3.0 mT static magnetic field (SMF) mediated the sensitization of breast cancer cells to TRAIL‐induced apoptosis. This effect was significantly reduced by the forced expression of survivin, suggesting the sensitization was mediated at least in part through the inhibition of survivin expression. In addition, SMF alone or in combination with TRAIL induced a cell cycle arrest within the G2/M phase, and the reduction in the survivin protein level was associated with the downregulated expression of Cdc2, a cyclin B‐dependent kinase that is necessary for the entry into the M phase. Taken together, our results demonstrated that SMF promoted TRAIL‐induced apoptosis by inhibiting the expression of Cdc2 and, subsequently, survivin. Of note, SMF did not sensitize untransformed human mammary epithelial cells to TRAIL‐mediated apoptosis. Therefore, the combined treatment of SMF and TRAIL may offer an attractive strategy for safely treating resistant breast cancers. Bioelectromagnetics. 35:337–346, 2014. © 2014 Wiley Periodicals, Inc.